1990
DOI: 10.1111/j.1469-8137.1990.tb00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of VA mycorrhizal fungi and rhizosphere microorganisms on acquisition of mineral nutrients by maize (Zea mays L.) in a calcareous soil

Abstract: SUMMARYMaize {Zea mays L.) was grown in a fertilized calcareous soil in pots which were separated by 30 /tm nylon nets into three compartments, a central one for root growth and two outer ones for hyphal growth. The treatments comprised of sterilised soil, either inoculated with rhizosphere microorganisms together with Glomus mosseae (Nicol. & Gerd.) Gerdemann & Trappe, with rhizosphere microorganisms alone, or non-inoculated (sterile control).In the mycorrhizal treatment concentrations of P and Zn were increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
2
12

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(73 citation statements)
references
References 32 publications
5
54
2
12
Order By: Relevance
“…City Beach to increase the concentration of Zn in clover plants and Cu in clover roots, but not in the shoots, compared with G. etunicatum, and to some extent G. mosseae, might result from their greater formation of external hyphae in compacted soil. A similar increase in the concentration of Cu in the roots upon mycorrhizal colonization has been shown for Zea mays (Kothari, Marschner & Ro$ mheld, 1990). The reason for the increase being observed only in mycorrhizal roots is not clear, but might be due to sequestration of Cu in the fungus, for example, via a chemical reaction between Cu and fungal polyphosphate granules, as has been shown for Ca and Fe by White & Brown (1979).…”
supporting
confidence: 69%
“…City Beach to increase the concentration of Zn in clover plants and Cu in clover roots, but not in the shoots, compared with G. etunicatum, and to some extent G. mosseae, might result from their greater formation of external hyphae in compacted soil. A similar increase in the concentration of Cu in the roots upon mycorrhizal colonization has been shown for Zea mays (Kothari, Marschner & Ro$ mheld, 1990). The reason for the increase being observed only in mycorrhizal roots is not clear, but might be due to sequestration of Cu in the fungus, for example, via a chemical reaction between Cu and fungal polyphosphate granules, as has been shown for Ca and Fe by White & Brown (1979).…”
supporting
confidence: 69%
“…Plants inoculated with AMF displayed good development and, hence, were more resistant to that stress because vascular cylinders are clogged and the root area decreases in plants infested by nematodes (Agrios, 1989). AMF provide benefits to the plant, likely through root hydration mechanisms strengthened or mediated by fungal hyphae (Hardie, 1985;Marulanda et al, 2003;Ruiz-Lozano and Azcón, 1995), facilitating mineral nutrient absorption (Varma, 1995) or through morphological changes in roots caused by AMF (Kothari et al, 1990). Such effects of mycorrhizae enable plants to maintain a better hydration and nutrition status at all times, even in the presence of the parasite (Augé, 2001).…”
Section: The Response Of Growth Variablesmentioning
confidence: 99%
“…Studies have indicated that AM fungi can increase the activities of soil enzymes such as phosphatase and dehydrogenase (Dodd et al, 1987;Kothari et al, 1990;Vá zquez et al, 2000). Dehydrogenase, a soil oxidoreductase, is an intracellular enzyme catalyzing oxidoreduction reactions of organic compounds.…”
Section: Introductionmentioning
confidence: 99%